Islamic Religious Education Reform In Indonesia In The Millennial Era - Wibowo, Raditya; Iqbal Khalid, Muhammad; Rizkina Fadhilah, Dinda; Nasabilah Zahrani, Isnaini; Gymnastiar Ramadhan, Farell; Muhammad Noor, Aditia (At-Tuhfah : Jurnal Studi Keislaman, 2024)
This article aims to discuss the challenges and opportunities faced in responding to the increasingly complex and diverse needs of Islamic education for the millennial generation. Islamic religious education in Indonesia plays a crucial role in shaping the character of today's youth while also fostering scientific skills. The reform of Islamic education in Indonesia during the millennial generation era is needed to build a generation with noble character and Islamic values. Therefore, Islamic religious education in Indonesia must be made a primary priority. Islamic religious education is expected to shape educated students who are well-versed in Islamic teachings, able to apply them in daily life, and contribute to creating a more moral society and building the resilience of Muslims in an increasingly complex era.